Why Japan isn’t more attractive to highly-skilled migrants - Morita, Liang (Cogent social sciences, 2017)
In May 2012, Japan launched the Point-Based Preferential Immigration Treatment for Highly-Skilled Professionals system for highly-skilled migrants. This launch is a culmination of years of interest in attracting highly-skilled migrants. Although the incentives offered to highly-skilled migrants are attractive, incentives alone do not constitute the whole picture. Researchers such as Anthony D’Costa and Oishi Nana have written about why Japan is not attracting as many highly-skilled migrants as it could be. The present paper discusses Japanese exclusionary tendencies which diminish its attraction as a destination for highly-skilled migrants, focusing on its English language education, Nihonjinron influences, mistrust of foreigners, inequality between foreigners and the Japanese, and insistence on doing things the Japanese way. These issues need to be addressed if Japan is serious about attracting larger numbers of highly-skilled migrants.